Current trends in the application of non-invasive genetic sampling to study Neotropical birds: Uses, goals, and conservation potential. Issue 4 (November 2019) - Baus, Isaura; Miño, Carolina Isabel; Monge, Otto
The non-invasive collection of biological samples has proven useful to study a diverse array of research topics worldwide. Here, we present a systematic bibliographical synthesis exploring how the non-invasive collection of genetic samples has been used to study avian populations in the Neotropics. We searched international online databases for scientific publications, spanning from 2007 to 2017, to describe the trends and identify the sample types used, species studied, and research questions addressed. The analysis of 21 articles showed that shed feathers were most frequently used (66.7% of articles), followed by carcasses (14.2%), eggs (9.5%), and non-invasively obtained blood (4.8%); one study used both feces and shed feathers. Most studies addressed population genetic issues (38.1%), followed by species identification (28.6%), phylogenetic questions (14.3%), molecular sexing (9.5%), and parentage analyses (9.5%). Brazil produced almost half (47.6%) of the publications retrieved. Despite an increasing interest in using non-invasive sampling to study Neotropical avifauna, its application is still largely concentrated in the most developed countries in this region and to explore a limited number of questions. A more regular use of non-invasive sampling would help advance the knowledge of ecological, behavioral, genetic, and evolutionary aspects of Neotropical birds. Investigating the extent of human–wildlife conflict, such as impact of road-kills, illegal traffic, and collision with aerial infrastructure or unmanned vehicles, is an underexplored avenue of research in which this method could be of much help. Non-invasive genetic sampling can help tackle conservation problems and pave the way to scientifically informed conservation policies in this avian biodiversity hotspot.